Tauhid Al-Wujud Syeikh Siti Jenar dan Unio Mystica Bima - Utomo, Agus Himawan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
Islam and Java tradition believe that the human beingconsisted of physic (material) and soul/suksma (immaterial) whichis immortal. Human develop relation to the Creator by the mindand self practice to sanctify their self and bunch up with the God.The uniqueness of Siti Jenar and Bima, in the relation to God, iscoalescing to God. Both of them are monism-idealism. Siti Jenar ofmystical union consists of essence and nature of God, according toSiti Jenar this world is death. While mystical union of Bima just innature of God, and the world is properly to fight. Javanese culturedo not detached of the others cultural opinion influence include ofmystique area. Â